2017
DOI: 10.1515/aiht-2017-68-3054
|View full text |Cite
|
Sign up to set email alerts
|

How protein coronas determine the fate of engineered nanoparticles in biological environment

Abstract: Nanomedicine is a booming medical field that utilises nanoparticles (NPs) for the development of medicines, medical devices, and diagnostic tools. The behaviour of NPs in vivo may be quite complex due to their interactions with biological molecules. These interactions in biological fluids result in NPs being enveloped by dynamic protein coronas, which serve as an interface between NPs and their environment (blood, cell, tissue). How will the corona interact with this environment will depend on the biological, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Colloidal stability and behavior of these AgNPs in different biological media were subject of our previous studies and reported elsewhere [ 24 , 25 , 26 ]. The presence of proteins in the media provided excellent colloidal stability regardless of the chemical composition, surface structure and surface charge of AgNPs due to the protein corona formation on the nanosurface [ 27 ]. As hPBMC isolates were dispersed in PBS before treatment, stability of AgNPs was inspected in this medium.…”
Section: Resultsmentioning
confidence: 99%
“…Colloidal stability and behavior of these AgNPs in different biological media were subject of our previous studies and reported elsewhere [ 24 , 25 , 26 ]. The presence of proteins in the media provided excellent colloidal stability regardless of the chemical composition, surface structure and surface charge of AgNPs due to the protein corona formation on the nanosurface [ 27 ]. As hPBMC isolates were dispersed in PBS before treatment, stability of AgNPs was inspected in this medium.…”
Section: Resultsmentioning
confidence: 99%
“…An important consequence of NPs interaction with biological environment is the formation of a biomolecular corona on their surface . In the resulting corona‐NPs complex, NPs may undergo different changes by means of their adsorption behavior, accumulation, degradation, agglomeration, dissolution, distribution, and clearance, but, more importantly, proteins and biomolecules from the corona may suffer from conformational changes, restructuration, and modification of their functional profile . The most studied corona‐NPs complexes are those related to the protein corona owing to the biological relevance of proteins .…”
Section: Introductionmentioning
confidence: 99%
“…Upon exposure to biofluids, the NPs acquire a "protein corona" due to the adherence of host proteins on the NPs surface. The composition of the corona is dependent on the types of nanoparticles and the biological sources [1][2][3] , and considered to provide the NPs with a "biological" identity 4 that affects stability, circulation time, and cellular uptake/interactions, and therefore has a strong impact on the functional role for the NPs [5][6][7][8][9][10] .…”
mentioning
confidence: 99%